Ambient air pollution and the health-related quality of life of older adults: Evidence from Shandong China. (15th June 2023) - Tan, Jialong; Chen, Nuo; Bai, Jing; Yan, Peizhe; Ma, Xinyu; Ren, Meiling; Maitland, Elizabeth; Nicholas, Stephen; Cheng, Wenjing; Leng, Xue; Chen, Chen; Wang, Jian
Abstract: Ambient air pollution is a major public health concern impacting all aspects of human health. There is a lack of studies on the impact of ambient air pollution on health-related quality of life (HRQoL) of older Chinese adults. Our study answers two questions: How concentrations of ambient air pollutants are associated with HRQoL among older adults in China and, second, what are the possible mechanisms through which ambient air pollution affects HRQoL. From the 2018 National Health Service Survey, we sampled 5717 aged 65 years or older residents for the eastern province of Shandong, China. Data on individual exposures to PM2.5 and PM10 (particulate matter with diameter less than or equal to 2.5 μm and 10 μm) and sulfur dioxide (SO2 ) were collected from the ChinaHighAirPollutants (CHAP) datasets. Mixed-effects Tobit regression models and mixed-effects ordered Probit regression models were employed to examine the associations of long-term exposure to ambient air pollution with the European Quality of Life 5 Dimensions 3 Level Version (EQ-5D-3L) scale comprising mobility, self-care, usual activities, pain/discomfort, and anxiety/depression. Socioeconomic, demographic and behavioral factors relating to HRQoL were also examined. The results show that for each 1 μg/m 3 increase, EQ-5D-3L scores fell 0.002 for PM2.5 ; 0.001 for PM10 and 0.002 for SO2 . Long term exposure to PM2.5, PM10 and SO2 were also associated with increased prevalence of pain/discomfort and anxiety/depression. The reduced HRQoL effects of ambient air pollution were exacerbated by higher socioeconomic status (affluent, urban and higher level of education). Our findings suggested that HRQoL of older Chinese adults was not only associated with demographic, socioeconomic, and health-related factors, but also negatively correlated with air pollution, especially through increased pain/discomfort and anxiety/depression. The paper proposes policy recommendations. Graphical abstract: Image 1 Highlights: Ambient air pollution was associated with lower HRQoL among older adults in China. Long term air pollution was associated with increased prevalence of pain and anxiety. The reduced HRQoL effects was exacerbated by higher socioeconomic status.